A retrospective comparison of double-hooked locking plates versus non-locking plates in minimally invasive percutaneous plate osteosynthesis for the treatment of comminuted distal fibular fractures accompanied by tibial Pilon fractures - Liu, Jun-Hong; Zhang, Qiang; Wei, Guo-Hua; Liu, Liang; Mu, Xin; Li, Mao-Lin; Wu, Zong-De (Journal of orthopaedic surgery and research, 2023)
Surgical approach and fixation material are crucial in the treatment of comminuted distal fibular fractures accompanied by tibial Pilon fractures. This study compared the efficacy of double-hooked locking plates and anatomic plates in minimally invasive percutaneous plate osteosynthesis (MIPPO) for the treatment of comminuted distal fibular fractures accompanied by tibial Pilon fractures. Clinical data were collected from 96 patients diagnosed with comminuted distal fibular fractures accompanied by tibial Pilon fractures who had undergone MIPPO. Patients in the study group (n = 48) received double-hooked locking plate fixations and the control group (n = 48) received anatomical plate fixations. The operating time, intraoperative bleeding, length of hospital stays, full weight-bearing time, fracture healing time and complication rates in the two groups were compared. The quality of fracture reduction was evaluated using the Burwell-Chamley imaging scoring system; the ankle function was assessed based on the American Orthopaedic Foot and Ankle Society Ankle-Hindfoot Score. Patients in the study group had shorter operating time, less bleeding, significantly shorter hospital stays, and shorter time to full weight-bearing as well as fracture healing compared to the control group (P < 0.05). Additionally, the post-operative complication rates were significantly lower in the study group (6.16% vs. 22.92%) (P < 0.05), but there was no significant difference in the fracture reduction rate between the two groups (P > 0.05). Patients in the study group experienced better ankle recovery than those in the control group (93.75% vs. 75.00%) (P < 0.05). Double-hooked locking plates have advantages in the treatment of comminuted distal fibular fractures accompanied by tibial Pilon fractures during MIPPO due to their shorter operating time and less intraoperative bleeding, as well as shorter hospital stays, full weight-bearing time and fracture healing time, fewer complications and better ankle recovery. Therefore, double-hooked locking plates are worthy of clinical application.